Catalytic cracking of biomass tar using Ni nanoparticles embedded carbon nanofiber/porous carbon catalysts. (1st February 2021) - Zhang, Shuping; Yin, Haoxin; Wang, Jiaxing; Zhu, Shuguang; Xiong, Yuanquan
Abstract: The major obstacles for catalytic cracking of biomass tar have been known as the low tar removal efficiency and catalyst deactivation. In view of this, the novel Ni nanoparticles embedded carbon nanofiber/porous carbon catalysts were synthesized by the method of hydrothermal treatment combined with carbothermal reduction. The properties of catalysts were evaluated by characterization of N2 adsorption-desorption, SEM, XRD, TEM, H2 -TPRand Raman, meanwhile the evolutionary mechanism of catalysts was also proposed. The tar catalytic cracking tests indicated that the Ni0.30 @CF/PCs exhibited the favorable catalytic activity with the high tar conversion efficiency (94.78%) as well as the better catalytic stability at the catalytic cracking temperature of 700 °C compared to other catalysts. In the case of Ni0.30 @CF/PCs, the carbon nanofiber/porous carbon composites with hierarchical micro-mesoporous structure and high graphitization degree as well as the Ni nanoparticles embedded in catalyst support with the strong metal-support interaction exhibited the favorable activity-structure relationship. In addition, the Ni0.30 @CF/PCs catalyst also presented the high tar conversion efficiency of 93.31% after 10 cycles, which was due to the high resistance towards coke deposition and sintering of metallic Ni covered by graphite layer from the carbothermal reduction process. Graphical abstract: Image 1 Highlights: Ni nanoparticles embedded carbon nanofiber/porous carbon catalyst was synthesized. Ni nanoparticles embedded in support showed the strong metal-support interaction. Ni0.30 @CF/PCs exhibited the favorable catalytic activity and stability. Ni0.30 @CF/PCs reached a high tar conversion efficiency of 94.78%.